PERBEDAAN PENGETAHUAN CARA MENYIKAT GIGI SEBELUM DAN SESUDAH DILAKUKAN PENYULUHAN DENGAN MEDIA RODA PUTAR (Roulatte) PADA SISWA MTsN 3 HULU SUNGAI TENGAH - Raudatul Septia Anggraini; Waljuni Astu Rahman; Naning Kisworo Utami (Poltekkes Kemenkes Banjarmasin, 2021)
The national prevalence of dental and oral problems is 25.9%. In fact, in the teeth, it was found that most of the Indonesian population's dental behavior during bathing in the morning and evening showers was 76.6%. And those who teeth properly after eating and before going to bed at night for Indonesians were found to be 2.3%. Through outreach programs, they can increase knowledge and awareness of the importance of maintaining dental and oral health and can actively participate in improving self-care efforts. In addition, with counseling, a person can work himself in an effort to prevent teeth and mouth This study aims to determine the difference in knowledge of how to teeth before and before counseling with a swivel wheel (roulette). The research design used is